(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The central axis of this essay is limited to the identity context, addressing characteristics about its construction process. It enters into the Trans identity, which diverges from the binary ideal (male / female) historically imposed as a standard in society. Different perspectives of difference and how this category is presented in the experiences of the identities mentioned above are analyzed. The methodology mixes analysis and interpretation. The analysis clarifies concepts, especially identity and difference. Through hermeneutics, these concepts are interpreted for an understanding in which cracks open to the optics of alterity and to a look that transcends the binary perspective.